2019
DOI: 10.1111/bcp.14034
|View full text |Cite
|
Sign up to set email alerts
|

The impact of liver transplant recipient and donor genetic variability on tacrolimus exposure and transplant outcome

Abstract: This study investigated the effect of recipient and donor genetic variability on dose‐adjusted steady‐state tacrolimus concentrations (Css) and clinical outcomes 3 and 6 months after liver transplant. Twenty‐nine recipients and matched donor blood samples were genotyped for 27 single nucleotide polymorphisms including CYP3A5*3 (rs776746), ABCB1 haplotype and immune genes. Associations between genetic variability and clinical parameters and Css and the occurrence of rejection and nephrotoxicity were analysed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…CYP3A5*3 (rs776746) mutation results in nonfunctional protein, leading to decreased CYP3A5 activity [8]. And hence, CYP3A5*3/*3 genotype carriers are reported to require lower doses, and exhibit higher dose adjusted trough concentration (C/D) of Tac when compared to CYP3A5*1 carriers in kidney [9], liver [10], and heart transplantation recipients [11]. In LTx, similar results have been reported in Caucasians [12][13][14].…”
Section: Introductionmentioning
confidence: 60%
“…CYP3A5*3 (rs776746) mutation results in nonfunctional protein, leading to decreased CYP3A5 activity [8]. And hence, CYP3A5*3/*3 genotype carriers are reported to require lower doses, and exhibit higher dose adjusted trough concentration (C/D) of Tac when compared to CYP3A5*1 carriers in kidney [9], liver [10], and heart transplantation recipients [11]. In LTx, similar results have been reported in Caucasians [12][13][14].…”
Section: Introductionmentioning
confidence: 60%
“…However, probably due to a limited sample size (see Table 2), the impact of -6331T > C on BPAR incidence was not statistically significant after adjusting for multiple comparisons. Although a recent liver transplant study also failed to show a significant relationship between -6331T > C and BPAR incidence, its sample size was even smaller (liver transplant recipient and donor n = 29; BPAR n = 8), and there were no recipients with the -6331 C/C genotype (Coller et al, 2019). Therefore, the impact of the IL6 -6331T > C on inflammation and BPAR incidence is still uncertain, and more studies with larger sample sizes are needed to elucidate if this SNP affects BPAR incidence in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 95%
“…Genomic DNA was extracted from blood, buccal swab, and kidney tissue (Hu et al, 2018;Hu et al, 2019a). A panel of 21 SNPs in 15 genes described previously (Mulholland et al, 2014;Barratt et al, 2015;Coller et al, 2015;Somogyi et al, 2016;Coller et al, 2019) were assayed using Agena Bioscience (formerly known as Sequenom) MassARRAY at the Australian Genome Research Facility (Brisbane, Australia). This panel included SNPs in the MyD88-dependent TLR signaling pathway-TLR2 1350T > C (rs3804100), TLR4 896A > G and 1196C > T, and MYD88 1593A > G (rs6853); pro-and anti-inflammatory mediators-CASP1 5352G > A (rs580253) and 10643G > C (rs554344), CRP -717T > C (rs2794521), IL1B -511C > T (rs16944), -31T > C (rs1143627), and -3954C > T, IL2 -330T > G, IL6 -6331T > C (rs10499563), IL6R -48892A > C (rs8192284), IL10 -1082G > A and -819C > T, TGFB -509C > T (rs1800469), and TNF -308G > A.…”
Section: Genotypingmentioning
confidence: 99%
“…However, the association between various single nucleotide polymorphisms of ABCB1 and tacrolimus pharmacokinetics in liver transplantation is debated. Wei‐lin et al demonstrated the importance of polymorphisms of intestinal (recipient) ABCB1, 8 whereas no appreciable influence of either liver (donor) or intestinal (recipient) ABCB1 genotypes on tacrolimus dose‐requirement or concentration/dose ratios was found by other authors 9–12 . In recipients, tacrolimus exposure appears to depend on the hepatic and intestinal tacrolimus‐metabolizing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients carrying functional CYP3A5*1 allele can metabolize tacrolimus at high rates; therefore, in liver transplantation, the association between tacrolimus pharmacokinetics and CYP3A5 genotypes of both the liver (donor) and the intestine (recipient) has been investigated. In full‐size liver transplantation, tacrolimus concentration/dose ratios seem to be influenced by the donor CYP3A5 genotype rather than by the recipient in the early (<1 month after transplantation) and late postoperative period (> 1 month) 9,10,18,19 ; however, some authors have suggested that both the donor and the recipient CYP3A5 genotypes are of major impact on tacrolimus clearance 12,20 . In living‐donor liver transplantation, due to the fact that the grafted liver regenerates its mass and tacrolimus clearance gradually increases with post‐transplant time, the pharmacokinetics primarily affected by the intestinal (recipient) CYP3A5 genotype early after transplantation, and by the liver graft or by both the recipient and the donor genotypes at late postoperative time 21–25 .…”
Section: Introductionmentioning
confidence: 99%